Estudo da fragilização por hidrogênio em interfaces dissimilares de juntas soldadas - Carvalho, Mariana Georges Monteiro de. (2018)
The conjugation of materials with different chemical compositions, motivated by the need to conjugate their different properties, were the factors that led to the emergence of dissimilar joints. Dissimilar welded joints have been extensively studied by the oil and gas industry, primarily due to their wide applicability in the manufacture of subsea equipment, together with the fact that recent accidents were directly related to failures in this type of welded joint. In the present work, the performance of dissimilar joints to hydrogen embrittlement under cathodic protection were evaluated through two different methodologies: CTOD and SSRT. The welded joints are composed of base metals ASTM A182 grade F22 and API 5L grade X70 and the filler metal used was Inconel 625. Six different welding conditions were evaluated by modifying the heat input, post-weld heat treatment time (PWHT) and welding process. The results showed that the resistance to hydrogen embrittlement is related to the number of discontinuous regions (macrossegregations) present along the dissimilar interface and to the time of PWHT. Some aspects related to the methodologies used to evaluate the performance of these welded joints under cathodic protection were also analyzed.